The Impact of Workplace Interpersonal Conflict on Job Performance, Job Depression and Turnover Intention - Beenish Khan; Amir Azam (Budapest International Research and Critics University, 2022)
The objective of the current study is to check the impact of workplace interpersonal conflict’s impact on job performance, job depression and turnover intention. The current study is been set to make cross sectional analysis of employees working in both public and private organizations. A pre-planned and well-structured questioner is been designed and provided to 350 respondents. 215 respondents returned the fill questioners. Simple statistical tools are been used to find the demographic features and average behavior of the respondents. Regression technique is been used for hypothesis testing and inferential statistics. The findings of regression analysis showed the interpersonal conflicts reduces job performance. Increase in interpersonal conflict increase the job depression. The impact of interpersonal conflict on turnover intention is been observed positive and statistically significant at 1%. All three-null hypotheses are been rejected while alternative hypotheses are been accepted. The moderating and mediating factors i.e. organizational maturity and supervisor behavior help reducing the interpersonal conflicts. It is been suggested that the organization need to promote employees frankly strategies and policies.